Analisis Kritik Sastra Baru terhadap Penokohan Edmund Pevensie yang Menggambarkan Persoalan Self-Centeredness dalam Novel Berjudul The Lion, the Witch, and the Wardrobe - Hidayat, Nur Intan Manylanti (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2024)
Among various children's literary works, the famous novel